The differential effect of individual and collaborative processing of written corrective feedback on French as a foreign language learners’ engagement - Lira-Gonzales, Maria-Lourdes; Nassaji, Hossein; Chao Chao, Kuok-Wa (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée, 2025)
An increasing number of studies have explored the effects of collaborative writing on written outcomes; however, few studies have examined the influence of collaborative processing of feedback. This study addresses this gap by focusing on learner engagement. While collaborative writing involves co-authoring a text, which requires negotiation and idea sharing, collaborative processing of feedback focuses on jointly interpreting and responding to feedback. Utilizing a mixed-methods design, this study examined 24 learners of French as a Foreign Language (FFL) over an 8-week period. It compared their engagement with written corrective feedback (WCF) when processed individually versus in pairs. The findings provide insights into how different feedback processing modes influence learner engagement and highlight the potential benefits of collaborative feedback processing. The instructor provided indirect WCF, and learners revised their essays with think-aloud sessions. The study examined cognitive and behavioral engagement through writing analysis and used think-aloud reports examining affective engagement. Results indicated that learners’ cognitive engagement varied between individual and collaborative processing, with individuals employing fewer high-depth and low-depth processing strategies. However, affective engagement was found to be independent of task completion mode, and behavioral engagement did not differ between individual and collaborative processing of WCF.